A fe-n-c bifunctional catalyst with enhanced pi conjugation and a preparation method and application thereof

By regulating the π-conjugation effect of Fe-NC catalyst, a highly efficient and stable oxygen reduction/oxygen evolution reaction catalyst was prepared, which solved the problem of limited performance of existing catalysts and is suitable for energy conversion devices such as fuel cells and metal-air batteries.

CN120511313BActive Publication Date: 2025-11-28INNER MONGOLIA UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510999334.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-21
Publication Date
2025-11-28
Estimated Expiration
2045-07-21

AI Technical Summary

Technical Problem

The electrochemical performance of existing Fe-NC catalysts in oxygen reduction and oxygen evolution reactions is limited, especially since the π-conjugation effect cannot be effectively controlled, resulting in high catalyst cost and poor performance.

Method used

Fe-NC catalysts were prepared by regulating the π-conjugation effect of organic ligands with benzene rings and/or heterocycles using inorganic salts. The catalysts with enhanced π-conjugation effect were formed through solid-phase melting reaction and calcination, thereby improving electron density and stability.

Benefits of technology

It achieves excellent electrocatalytic performance for oxygen reduction and oxygen evolution reactions under alkaline conditions, reduces costs and improves catalyst stability, and is suitable for energy conversion devices such as fuel cells and metal-air batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120511313B_ABST
    Figure CN120511313B_ABST
Patent Text Reader

Abstract

The application discloses a Fe-N-C bifunctional catalyst with enhanced pi conjugation and a preparation method and application thereof. The application controls the pi conjugation effect of an organic ligand with a benzene ring and / or a heterocyclic ring by using inorganic salts, and synthesizes a high-efficiency and stable Fe-N-C oxygen reduction / oxygen evolution reaction bifunctional catalyst. The bifunctional catalyst has excellent oxygen reduction / oxygen evolution reaction electrocatalytic performance and stability under alkaline conditions, and has the advantages of simple preparation method, rich raw material sources, easy industrial production and low cost, and therefore has a wide application prospect in energy conversion devices such as fuel cells and metal-air batteries.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of catalyst preparation, and particularly relates to a Fe-N-C bifunctional catalyst with enhanced pi conjugation and a preparation method and application thereof. BACKGROUND

[0002] To cope with the environmental pollution problems such as more CO2 emissions caused by traditional fossil energy and the problems of region and climate caused by new wind energy and solar energy, promoting energy transformation and green low-carbon transformation of energy terminal has become the focus of research of countries all over the world. Metal-air batteries and other various fuel cells as the energy conversion devices currently researched more, can convert clean energy into electric energy and ultimately be applied to vehicle-mounted, aviation and other fields, so as to reduce carbon pollution and improve energy utilization rate, but require the energy conversion device to have high power density and conversion efficiency. The cathode oxygen reduction reaction (Oxygen Reduction Reaction, ORR) and oxygen evolution reaction (Oxygen Evolution Reaction) involve multiple proton-coupled-electron transfer steps, and have slow reaction kinetics. In order to accelerate the reaction kinetics of these steps, currently, expensive Pt / C catalysts are mainly used, which leads to a substantial increase in system cost. Therefore, designing and constructing high-performance and low-cost ORR / OER catalysts has always been the focus of research in the relevant field.

[0003] Porous carbon is widely used in energy storage and conversion devices due to its ability to provide more metal coordination sites, sufficient electron transport and better stability. To improve the problem of uniform electron cloud density around carbon, doping N elements with different electronegativity can effectively improve the ORR / OER performance of carbon-based catalysts. Carbon-based Fe-N-C catalysts derived from transition metal Fe as active center have attracted attention due to their comparable ORR / OER electrochemical performance to Pt / C catalysts and inexpensive preparation process. With the development of theoretical research and advanced characterization techniques, FeN4-C 10 and FeN4-C 12 are considered to be the main active sites for ORR / OER. This also proves the important influence of the C environment around the Fe-N coordination center on its electrocatalytic activity.

[0004] In recent years, more and more studies have shown that the π-conjugation effect of the carbon skeleton of the Fe-N-C catalyst cannot be ignored for the ORR / OER performance, because the π-conjugation effect of the carbon skeleton can enrich the electron density of the Fe center, enhance the electron transfer rate, and improve the stability of the catalyst. Chinese Patent Application CN114899436A discloses a preparation method of a phthalocyanine-like polymer carbon-derived Fe / N / C oxygen reduction catalyst, which uses iron and zinc for metal coordination, and uses a large amount of Zn ions for spatial isolation, so that the Fe ions are highly dispersed to form a large conjugated system of a phthalocyanine-like polymer. Although the electrostatic interaction between iron ions is weakened by the large conjugated system of the polymer, the specific structure of the phthalocyanine limits the influence of the π-conjugation effect on the electronic structure of the iron ions, ignores the influence of the O atom and the Fe coordination structure on the oxygen electrocatalytic reaction, and increases the difficulty of accurately controlling the doping amount. Moreover, the oxygen evolution reaction electrochemical performance is not mentioned.

[0005] Therefore, there is still a need to study how to controllably design the coordination structure of the active center of the Fe-N-C catalyst through the π-conjugation effect and systematically improve the ORR / OER electrochemical performance.

[0006] The information in the background art is merely intended to explain the general background of the application and should not be considered as admitting or implying in any form that the information constitutes prior art known to those skilled in the art. SUMMARY

[0007] To solve at least part of the technical problems in the prior art, the present application adjusts the π-conjugation effect of the organic ligand with a benzene ring and / or a heterocyclic ring by inorganic salt to obtain a precursor, and further copolymerizes the precursor with an iron compound to obtain a Fe-N-C oxygen reduction / oxygen evolution reaction bifunctional catalyst with more uniform iron element doping and a larger doping amount. In addition, the present application improves the electrocatalytic performance and stability of the Fe-N-C oxygen reduction / oxygen evolution reaction bifunctional catalyst by adjusting the degree of π-conjugation effect. Specifically, the present application includes the following contents.

[0008] In a first aspect of the present application, a preparation method of a Fe-N-C bifunctional catalyst with enhanced π-conjugation effect is provided, which comprises the following steps:

[0009] (1) obtaining a covalent organic framework containing π-conjugation effect by solid-phase melting reaction of a dianhydride and a diamine in the presence of anhydrous inorganic salt;

[0010] (2) mixing the covalent organic framework with an iron compound to obtain a mixture;

[0011] (3) calcining the mixture at 700-1100°C to obtain a Fe-N-C oxygen reduction / oxygen evolution reaction bifunctional catalyst with enhanced π-conjugation effect.

[0012] In certain embodiments, the method for preparing the π-conjugation enhanced Fe-N-C bifunctional catalyst according to the present application, wherein, in step (1), the temperature of the solid-phase melting reaction is 100-450 °C, and the time is 1-50 h.

[0013] In certain embodiments, the method for preparing the π-conjugation enhanced Fe-N-C bifunctional catalyst according to the present application, wherein, in step (1), the anhydrous inorganic salt comprises at least one of anhydrous zinc chloride, anhydrous sodium chloride, or anhydrous calcium chloride.

[0014] In certain embodiments, the method for preparing the π-conjugation enhanced Fe-N-C bifunctional catalyst according to the present application, wherein, in step (1), the dianhydride comprises at least one of pyromellitic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, perylene 3,4,9,10-tetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 1,2,3,4-cyclopentanetetracarboxylic dianhydride, or 1,2,3,4-cyclobutanetetracarboxylic dianhydride.

[0015] In certain embodiments, the method for preparing the π-conjugation enhanced Fe-N-C bifunctional catalyst according to the present application, wherein, in step (1), the diamine comprises at least one of melamine, phenylenediamine, benzimidazole diamine, 2,6-diaminopyridine, 2,4,6-triaminopyrimidine, 4,4'-diaminodiphenylmethane, or 2,2-bis[4-(4-aminophenoxy)phenyl]propane.

[0016] In certain embodiments, the method for preparing the π-conjugation enhanced Fe-N-C bifunctional catalyst according to the present application, wherein the molar ratio of the dianhydride, the diamine, and the anhydrous inorganic salt is 1:(1-10):(5-15).

[0017] In certain embodiments, the method for preparing the π-conjugation enhanced Fe-N-C bifunctional catalyst according to the present application, wherein, in step (2), the iron compound comprises at least one of ferric chloride, ferric nitrate, ferric sulfate, iron oxide, or magnetite.

[0018] In certain embodiments, the method for preparing the π-conjugation enhanced Fe-N-C bifunctional catalyst according to the present application, wherein, in step (2), the mixing comprises at least one of a hydrothermal method, an impregnation method, or a distillation stirring reflux method.

[0019] In certain embodiments, the method for preparing the π-conjugation enhanced Fe-N-C bifunctional catalyst according to the present application, wherein the calcination time in step (3) is 2-10 h. In certain embodiments, the method for preparing the π-conjugation enhanced Fe-N-C bifunctional catalyst according to the present application, wherein the calcination time in step (3) is 2-10 h.

[0020] In a second aspect, the present application provides a π-conjugation enhanced Fe-N-C bifunctional catalyst prepared by the preparation method of the first aspect of the present application.

[0021] In a third aspect, the present application provides use of the π-conjugation enhanced Fe-N-C bifunctional catalyst according to the second aspect of the present application in an energy conversion device.

[0022] The present application synthesizes a high-efficiency and stable Fe-N-C oxygen reduction / oxygen evolution reaction bifunctional catalyst by regulating the π-conjugation effect of an organic ligand having a benzene ring and / or a heterocyclic ring by an inorganic salt, and further copolymerizing the precursor with an iron compound. The π-conjugation effect can enrich the electron density of Fe center, enhance the electron transfer rate, and improve the stability of the catalyst. The bifunctional catalyst of the present application exhibits excellent oxygen reduction / oxygen evolution reaction electrocatalytic performance (e.g., lower overpotential, higher current density, etc.) and stability under alkaline conditions, and has the advantages of simple preparation method, abundant raw material sources, easy industrial production, low cost, etc. Therefore, the bifunctional catalyst has a broad application prospect in energy conversion devices such as fuel cells and metal-air batteries. BRIEF DESCRIPTION OF DRAWINGS

[0023] Figure 1 Scanning electron microscope images of Fe-N-C oxygen reduction / oxygen evolution reaction bifunctional catalysts prepared in Examples 1, 2, and 3 of the present application.

[0024] Figure 2 Powder X-ray diffraction spectra of Fe-N-C oxygen reduction / oxygen evolution reaction bifunctional catalysts prepared in Examples 1, 2, and 3 of the present application.

[0025] Figure 3 Oxygen reduction reaction electrochemical performance diagrams of Fe-N-C oxygen reduction / oxygen evolution reaction bifunctional catalysts prepared in Examples 1, 2, and 3 of the present application and Comparative Examples 1 and 2.

[0026] Figure 4 Oxygen evolution reaction electrochemical performance diagrams of Fe-N-C oxygen reduction / oxygen evolution reaction bifunctional catalysts prepared in Examples 1, 2, and 3 of the present application and Comparative Example 3.

[0027] Figure 5 Zinc-air battery performance diagram of the Fe-N-C oxygen reduction / oxygen evolution reaction bifunctional catalyst of the present application. DETAILED DESCRIPTION

[0028] Various exemplary embodiments of the present application will now be described in detail, which should not be considered as limiting the present application, but rather as a description of certain aspects, features, and embodiments of the present application.

[0029] It is to be understood that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the present application. Additionally, for a range of values of, for example, a parameter, an individual value from the range as well as intermediate values should be understood as being included in the present application. Each intermediate value within the implied range, and any other stated or intervening value(s) between any stated value and an intervening value, should be included as well. The upper and lower limits of these smaller ranges can independently be included or excluded in the range.

[0030] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. Although preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present application. All documents mentioned herein are incorporated by reference to disclose and describe the methods and / or materials in connection with which the documents are cited. In case of conflict, the content of the present specification will control.

[0031] Preparation method

[0032] In one aspect of the present application, a method for preparing a π-conjugation enhanced Fe-N-C bifunctional catalyst is provided. In a preferred embodiment, the method for preparing the present application comprises the following steps:

[0033] (1) obtaining a covalent organic framework containing π-conjugation effect by solid-state melt reaction of a dianhydride and a diamine in the presence of anhydrous inorganic salt, wherein the temperature of the solid-state melt reaction is 100-450 °C, preferably 150-400 °C, more preferably 200-350 °C, even more preferably 250-350 °C, for example 255, 260, 265, 270, 275, 280, 285, 290, 300, 305, 310, 315, 320, 325, 330, 335, 340, 345, 350, 360 °C, the heating rate is 1-10 °C / min, for example 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 °C / min, and the time is 1-50 h, preferably 1-40 h, more preferably 1-35 h, even more preferably 1-30 h, even more preferably 1-20 h, for example 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 h; -1

[0034] (2) mixing the covalent organic framework with an iron compound to obtain a mixture;

[0035] ​(3) calcining the mixture at 700-1100℃ for 2-10 h to obtain the Fe-N-C oxygen reduction / oxygen evolution reaction bifunctional catalyst with enhanced π conjugation effect.

[0036] It can be understood that, in step (1) of the present application, in order to better perform the solid-phase melting reaction, the raw materials such as the anhydrous inorganic salt, the dianhydride, and the diamine can be subjected to a mixing operation such as grinding before the reaction. In addition, the covalent organic framework can be subjected to a step of washing and freeze-drying before being mixed with the iron compound, and the washing agent is not particularly limited, examples of which include but are not limited to 0.05-5 mol / L of HCl, tetrahydrofuran, distilled water, etc., and the time for freeze-drying is not particularly limited, for example, 5-72 h.

[0037] In order to regulate the π conjugation effect and further improve the electrocatalytic performance and stability of the Fe-N-C oxygen reduction / oxygen evolution reaction bifunctional catalyst, in step (1) of the present application, the molar ratio of the dianhydride, the diamine, and the anhydrous inorganic salt can be controlled within a suitable range. In a preferred embodiment, the molar ratio of the dianhydride, the diamine, and the anhydrous inorganic salt is 1:(1-10):(5-15), preferably 1:(1-8):(5-15), more preferably 1:(1-6):(5-15), further preferably 1:(1-6):(5-12), more preferably 1:(1-6):(5-10), for example, 1:1:5, 1:1:6, 1:1:7, 1:1:8, 1:1:9, 1:1:10, 1:2:5, 1:2:6, 1:2:7, 1:2:8, 1:2:9, 1:2:10, 1:3:5, 1:3:6, 1:3:7, 1:3:8, 1:3:9, 1:3:10, 1:4:5, 1:4:6, 1:4:7, 1:4:8, 1:4:9, 1:4:10, 1:5:5, 1:5:6, 1:5:7, 1:5:8, 1:5:9, 1:5:10, 1:6:5, 1:6:6, 1:6:7, 1:6:8, 1:6:9, 1:6:10, or any value within the above ranges. In a most preferred embodiment, the molar ratio of the dianhydride, the diamine, and the anhydrous inorganic salt is 1:2:8.4.

[0038] In the present application, the anhydrous inorganic salt is not particularly limited, examples of which include but are not limited to anhydrous zinc chloride, anhydrous sodium chloride, anhydrous calcium chloride, etc. In a preferred embodiment, the anhydrous inorganic salt is anhydrous zinc chloride.

[0039] In the present application, the dianhydride is not particularly limited, and examples thereof include, but are not limited to, pyromellitic dianhydride, 1,4,5,8-naphthalene tetracarboxylic anhydride, perylene 3,4,9,10-tetracarboxylic dianhydride, 3,3',4,4'-biphenyl tetracarboxylic dianhydride, 1,2,3,4-cyclopentane tetracarboxylic dianhydride, 1,2,3,4-cyclobutane tetracarboxylic dianhydride, and the like. In a preferred embodiment, the dianhydride is pyromellitic dianhydride. In another preferred embodiment, the dianhydride is 1,4,5,8-naphthalene tetracarboxylic dianhydride. In still another preferred embodiment, the dianhydride is perylene 3,4,9,10-tetracarboxylic dianhydride.

[0040] In the present application, the diamine is not particularly limited, and examples thereof include, but are not limited to, melamine, phenylenediamine, benzimidazole diamine, 4,4'-diaminodiphenyl methane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,6-diaminopyridine, 2,4,6-triaminopyrimidine, and the like. In a preferred embodiment, the diamine is melamine.

[0041] In the present application, the iron compound is not particularly limited, and examples thereof include, but are not limited to, ferric chloride, ferric nitrate, ferric sulfate, iron oxide, ferroferric oxide, and the like. In a preferred embodiment, the iron compound is ferric nitrate.

[0042] In step (2) of the present application, the mixing is not particularly limited, and examples thereof include a hydrothermal method, an impregnation method, a distillation stirring reflux method, and the like. In a preferred embodiment, the mixing comprises stirring mixing the covalent organic framework with an aqueous solution of an iron compound, centrifuging, and drying to obtain the gray-green solid, wherein the stirring time is 20-100 h, preferably 30-90 h, more preferably 40-80 h, for example 40, 42, 44, 46, 48, 50, 52, 54, 56, 58, 60, 62, 64, 66, 68, 70, 72, 74, 76, 78, 80 h; the centrifuging is preferably performed at a speed of 5000-10000 r / min, preferably 6000-9000 r / min, more preferably 7000-8500 r / min, for example 7000, 7100, 7200, 7300, 7400, 7500, 7600, 7700, 7800, 7900, 8000, 8100, 8200, 8300, 8400, 8500 r / min, for 1-20 min, preferably 1-15 min, more preferably 1-10 min, for example 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 min, and the number of centrifuging is not particularly limited, for example 1, 2, 3, 4, 5, 6 times, and the washing liquid is not particularly limited, and examples thereof include, but are not limited to, N-methylpyrrolidone, anhydrous ethanol, distilled water, and the like. In a preferred embodiment, the centrifuging comprises centrifuging at a speed of 8000 r / min for 5 min, with N-methylpyrrolidone, anhydrous ethanol, and distilled water as the washing liquid, respectively, and each washing liquid is repeated 3 times.

[0043] In order to improve the doping of iron elements, the dispersion performance of iron elements, control the strength of π conjugation effect, and improve the electrocatalytic performance and stability of the Fe-N-C oxygen reduction / oxidation reaction bifunctional catalyst, the amount of the covalent organic framework should not be too high or too low. In the present application, the amount of the covalent organic framework is 5-500 mg, preferably 10-400 mg, more preferably 20-300 mg, further preferably 30-200 mg, more preferably 40-100 mg, for example 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100 mg, relative to 1-4 mmol of Fe 3+ ions.

[0044] In order to obtain the Fe-N-C oxygen reduction / oxygen evolution reaction bifunctional catalyst with excellent electrocatalytic performance and stability, the suitable calcination conditions need to be controlled in step (3) of the present application, the calcination temperature is 700-1100°C, preferably 750-1050°C, and more preferably 800-1000°C, for example 800°C, 820°C, 840°C, 860°C, 880°C, 900°C, 920°C, 940°C, 960°C, 980°C, 1000°C, the calcination time is 2-10 h, for example 2, 3, 4, 5, 6, 7, 8, 9, 10 h, the temperature rising rate is 2-10°C / min, for example 2, 3, 4, 5, 6, 7, 8, 9, 10°C / min, and the like, but not limited to the listed values, and other values not listed in the range are also applicable. In a preferred embodiment, the calcination is calcination at 900°C for 3 h, and the temperature rising rate is 5°C / min.

[0045] In the present application, the solid phase melting reaction and calcination are preferably carried out under a protective atmosphere, which is not particularly limited, and examples thereof include, but are not limited to, high-purity nitrogen, high-purity argon, hydrogen-argon mixed gas, and the like. In a preferred embodiment, the protective atmosphere is nitrogen.

[0046] Bifunctional catalyst

[0047] In one aspect of the present application, a π-conjugation enhanced Fe-N-C oxygen reduction / oxygen evolution reaction bifunctional catalyst is provided, which is prepared by the preparation method of the present application.

[0048] In a preferred embodiment, the π-conjugation enhanced Fe-N-C oxygen reduction / oxygen evolution reaction bifunctional catalyst of the present application has a half-wave potential of not less than 0.825 V and an overpotential of not more than 651.6 mV.

[0049] Application

[0050] In one aspect of the present application, the use of the π-conjugation enhanced Fe-N-C bifunctional catalyst in an energy conversion device is provided.

[0051] In the present application, the energy conversion device includes a battery, wherein the battery is not particularly limited, and examples thereof include, but are not limited to, a fuel cell, a metal-air battery, and the like.

[0052] The π-conjugation enhanced Fe-N-C oxygen reduction / oxygen evolution reaction bifunctional catalyst of the present application also has high electrocatalytic performance and stability under alkaline conditions, and can effectively improve the power generation performance of batteries such as fuel cells and metal-air batteries.

[0053] Example 1

[0054] The preparation method and performance test results of the Fe-N-C oxygen reduction / oxygen evolution reaction bifunctional catalyst with enhanced π conjugation are shown below.

[0055] 1. Preparation method

[0056] Step 1: 1 mmol of pyromellitic dianhydride, 2 mmol of melamine and 8.4 mmol of anhydrous zinc chloride were weighed and ground in a maroon mortar for 30 min;

[0057] Step 2: heating to 315℃ at a heating rate of 5℃ / min under N2 atmosphere for 8 h to obtain a black-green solid; -1

[0058] Step 3: the black-green solid was washed with 0.1 mol / L of HCl, tetrahydrofuran and distilled water for 3 times respectively, and then freeze-dried for 24 h to obtain a precursor;

[0059] Step 4: 300 mg of the precursor was weighed and mixed with 50 mL of 0.08 mol / L Fe(NO3)3·9H2O aqueous solution under magnetic stirring for 72 h, and then centrifuged and dried to obtain a gray-green solid. -1

[0060] Step 5: the gray-green solid was calcined at 900℃ under N2 atmosphere at a heating rate of 5℃ / min for 3 h to obtain a Fe-N-C-1 oxygen reduction / oxygen evolution reaction bifunctional catalyst.

[0061] 2. Performance test

[0062] Step I: 4 mg of the Fe-N-C-1 oxygen reduction / oxygen evolution reaction bifunctional catalyst was taken and added to 1000 μL of a dispersion liquid prepared from 250 μL of ethanol and 750 μL of distilled water, and then ultrasonicated for 20 min to form an ink-like slurry after adding 20 μL of nafion and ultrasonication for another 20 min;

[0063] Step II: 20 μL of the ink-like slurry was measured and dropped on the surface of a rotating disc electrode disc, and then waited for complete drying;

[0064] Step III: another 20 μL of the ink-like slurry was measured and dropped on a foamed nickel (1 cm×1 cm), and then waited for complete drying;

[0065] Step IV: platinum wire was used as a counter electrode, Ag / AgCl was used as a reference electrode, and the rotating disc electrode completely dried in step II was used as a working electrode, and the oxygen reduction reaction electrocatalytic performance of the sample was tested in 0.1 mol / L KOH aqueous solution, and the test results are as follows Figure 3 ​​The half-wave potential is 0.841 V vs. RHE as shown.

[0066] Step V: The oxygen evolution reaction electrocatalytic performance of the sample was tested in 0.1 mol / L KOH aqueous solution with a high-purity graphite carbon rod as a counter electrode, Ag / AgCl as a reference electrode, and the completely air-dried foam nickel in step III as a working electrode. The test results are shown in FIG. 2. Figure 4 The overpotential is 651.6 mV vs. RHE as shown.

[0067] Example 2

[0068] The preparation method and performance test results of the Fe-N-C oxygen reduction / oxygen evolution reaction bifunctional catalyst with enhanced π conjugation are shown below.

[0069] 1. Preparation method

[0070] Step 1: 1 mmol of 1,4,5,8-naphthalene tetracarboxylic dianhydride, 2 mmol of melamine, and 8.4 mmol of anhydrous zinc chloride were weighed and ground in a marquetry mortar for 30 min;

[0071] Step 2: The mixture was heated to 315°C at a heating rate of 5°C / min under N2 atmosphere for 8 h to obtain a black-green solid; -1

[0072] Step 3: The black-green solid was sequentially washed with 0.1 mol / L HCl, tetrahydrofuran, and distilled water for 3 times, and then freeze-dried for 24 h to obtain a precursor;

[0073] Step 4: 300 mg of the precursor was mixed with 50 mL of a 0.08 mol / L Fe(NO3)3·9H2O aqueous solution, and magnetically stirred for 72 h. After centrifugation and drying, a gray-green solid was obtained. -1

[0074] Step 5: The gray-green solid was calcined at 900°C at a heating rate of 5°C / min under N2 atmosphere for 3 h to obtain a Fe-N-C-2 oxygen reduction / oxygen evolution reaction bifunctional catalyst.

[0075] 2. Performance test

[0076] Step I: 4 mg of the Fe-N-C-2 oxygen reduction / oxygen evolution reaction bifunctional catalyst was added to 1000 μL of a dispersion liquid prepared from 250 μL of ethanol and 750 μL of distilled water, and ultrasonically treated for 20 min. After adding 20 μL of nafion and ultrasonically treating for another 20 min, an ink-like slurry was formed;

[0077] ​​Step II: 20 μL of the ink-like slurry was dropped on the surface of the rotating disc electrode disk and then waited for complete drying;

[0078] Step III: Another 20 μL of the ink-like slurry was dropped on the surface of the nickel foam (1 cm x 1 cm) and then waited for complete drying;

[0079] Step IV: The oxygen reduction reaction electrocatalytic performance of the sample was tested in 0.1 mol / L KOH aqueous solution with a platinum wire as a counter electrode, Ag / AgCl as a reference electrode, and the completely dried rotating disc electrode of step II as a working electrode, and the test results are shown in Figure 3 , and the half-wave potential was 0.827 V vs. RHE;

[0080] Step V: The oxygen evolution reaction electrocatalytic performance of the sample was tested in 0.1 mol / L KOH aqueous solution with a high-purity graphite carbon rod as a counter electrode, Ag / AgCl as a reference electrode, and the completely dried nickel foam of step III as a working electrode, and the test results are shown in Figure 4 , and the overpotential was 447.6 mV vs. RHE.

[0081] Example 3

[0082] The following shows the preparation method and performance test results of the Fe-N-C oxygen reduction / oxygen evolution reaction bifunctional catalyst with enhanced π conjugation effect.

[0083] 1. Preparation method

[0084] Step 1: 1 mmol of perylene-3,4,9,10-tetracarboxylic anhydride, 2 mmol of melamine, and 8.4 mmol of anhydrous zinc chloride were weighed and ground in a marume mortar for 30 min;

[0085] Step 2: The mixture was heated to 315℃ at a heating rate of 5℃·min -1 under N2 atmosphere for 8 h to obtain a black-green solid;

[0086] Step 3: The black-green solid was sequentially washed with 0.1 mol / L HCl, tetrahydrofuran, and distilled water for 3 times each, and then freeze-dried for 24 h to obtain a precursor;

[0087] Step 4: 300 mg of the precursor was mixed with 50 mL of a 0.08 mol·L -1 Fe(NO3)3·9H2O aqueous solution and magnetically stirred for 72 h, and then centrifuged and dried to obtain a gray-green solid.

[0088] Step 5: The grey-green solid was calcined at 900 °C for 3 h with a ramp rate of 5 °C / min under N2atmosphere to obtain Fe-N-C-3 oxygen reduction / oxygen evolution reaction bifunctional catalyst.

[0089] 2. Performance test

[0090] Step I: 4 mg of the Fe-N-C-3 oxygen reduction / oxygen evolution reaction bifunctional catalyst was taken into 1000 μL of dispersion solution prepared by 250 μL of ethanol and 750 μL of distilled water, and after ultrasonic treatment for 20 min, 20 μL of nafion was added and ultrasonic treatment was performed for another 20 min to form an ink-like slurry;

[0091] Step II: 20 μL of the ink-like slurry was measured and dropped on the surface of the rotating disc electrode disc, and then completely air-dried;

[0092] Step III: Another 20 μL of the ink-like slurry was measured and dropped on the foamed nickel (1 cm x 1 cm), and then completely air-dried;

[0093] Step IV: The platinum wire was used as the counter electrode, Ag / AgCl was used as the reference electrode, and the completely air-dried rotating disc electrode in step II was used as the working electrode, and the oxygen reduction reaction electrocatalytic performance of the sample was tested in 0.1 mol / L KOH aqueous solution, and the test results are shown in Figure 3 , and the half-wave potential was 0.825 V vs. RHE;

[0094] Step V: The high-purity graphite carbon rod was used as the counter electrode, Ag / AgCl was used as the reference electrode, and the completely air-dried foamed nickel in step III was used as the working electrode, and the oxygen evolution reaction electrocatalytic performance of the sample was tested in 0.1 mol / L KOH aqueous solution, and the test results are shown in Figure 4 , and the overpotential was 488.6 mV vs. RHE.

[0095] Comparative Example 1

[0096] The following shows the preparation method and performance test results of the oxygen reduction / oxygen evolution reaction bifunctional catalyst.

[0097] 1. Preparation method

[0098] Step 1: 1 mmol of pyromellitic dianhydride and 2 mmol of melamine were weighed and ground in a marquetry mortar for 30 min;

[0099] Step 2: The temperature was heated to 315 °C under N2atmosphere with a ramp rate of 5 °C / min -1 , and calcined for 8 h to obtain a yellow solid;

[0100] Step 3: The yellow solid was washed with 0.1 mol / L HCl, tetrahydrofuran and distilled water for 3 times, respectively, and then freeze-dried for 24 h to obtain the precursor;

[0101] Step 4: 300 mg of the precursor was mixed with 50 mL of 0.08 mol / L Fe(NO3)3·9H2O aqueous solution and magnetically stirred for 72 h, and then centrifuged and dried to obtain a brick red solid. -1

[0102] Step 5: The brick red solid was calcined at 900℃ for 3 h under N2 atmosphere at a heating rate of 5℃ / min to obtain the Fe-N-C-4 oxygen reduction / oxygen evolution reaction bifunctional catalyst.

[0103] 2. Performance test

[0104] Step I: 4 mg of the Fe-N-C-4 oxygen reduction / oxygen evolution reaction bifunctional catalyst was added into 1000 μL of a dispersion liquid prepared from 250 μL of ethanol and 750 μL of distilled water, and ultrasonicated for 20 min to form an ink-like slurry after adding 20 μL of nafion and ultrasonication for another 20 min;

[0105] Step II: 20 μL of the ink-like slurry was measured and dropped on the surface of a rotating disc electrode disc, and then waited for complete drying;

[0106] Step III: The platinum wire was used as the counter electrode, Ag / AgCl as the reference electrode, and the completely dried rotating disc electrode in step II as the working electrode, and the oxygen reduction reaction electrocatalytic performance of the sample was tested in 0.1 mol / L KOH aqueous solution, and the test results are shown in Figure 3 , and the half-wave potential was 0.705 V vs. RHE;

[0107] Comparative Example 2

[0108] The preparation method and performance test results of the oxygen reduction / oxygen evolution reaction bifunctional catalyst are shown below.

[0109] 1. Preparation method

[0110] Step 1: 1 mmol of perylene-3,4,9,10-tetracarboxylic anhydride, 2 mmol of melamine and 20 mmol of anhydrous zinc chloride were weighed and ground in a agate mortar for 30 min;

[0111] Step 2: The black green solid was obtained by calcining at a heating rate of 5℃·min -1 -1 to 315℃ under N2 atmosphere for 8 h;

[0112] ​Step 3: The black-green solid was washed with 0.1 mol / L HCl, tetrahydrofuran and distilled water for 3 times, respectively, and then freeze-dried for 24 h to obtain the precursor;

[0113] Step 4: 300 mg of the precursor was mixed with 50 mL of 0.08 mol / L Fe(NO3)3·9H2O aqueous solution and magnetically stirred for 72 h, and then centrifuged and dried to obtain a gray-green solid. -1

[0114] Step 5: The gray-green solid was calcined at 500℃ for 3 h and then at 900℃ for 3 h at a heating rate of 5℃ / min under N2 atmosphere to obtain the Fe-N-C-5 oxygen reduction / oxygen evolution reaction bifunctional catalyst.

[0115] 2. Performance test

[0116] Step I: 4 mg of the Fe-N-C-5 oxygen reduction / oxygen evolution reaction bifunctional catalyst was added into 1000 μL of a dispersion liquid prepared by mixing 250 μL of ethanol and 750 μL of distilled water, and ultrasonic treatment was performed for 20 min. Then 20 μL of nafion was added and ultrasonic treatment was performed for another 20 min to form an ink-like slurry;

[0117] Step II: 20 μL of the ink-like slurry was measured and dropped on the surface of a rotating disc electrode disc, and then completely dried;

[0118] Step III: The oxygen reduction reaction electrocatalytic performance of the sample was tested in 0.1 mol / L KOH aqueous solution by taking a platinum wire as a counter electrode, Ag / AgCl as a reference electrode, and the completely dried rotating disc electrode in Step II as a working electrode. The test results are shown in Figure 3 , and the half-wave potential is 0.737 V vs. RHE.

[0119] Comparative Example 3

[0120] The preparation method and performance test results of the oxygen reduction catalyst are shown below.

[0121] 1. Preparation method

[0122] (1) Synthesis of phthalocyanine-like polymer:

[0123] 1.56 g of 3,4,9,10-perylenetetracarboxylic dianhydride, 2.10 g of urea, 0.50 g of ammonium chloride, 0.08 g of ammonium molybdate, 2.05 g of zinc chloride and 0.08 g of iron chloride were thoroughly ground to obtain a mixture. Then the mixture was heated to 220℃ at a heating rate of 2℃ / min in a muffle furnace for 3 hours.

[0124] ​After cooling, the product was ultrasonically treated in a mixed solution of sodium hydroxide solution (concentration 0.1 mol / L), ethanol and acetone (volume ratio 1:1:1) for 30 minutes, and then purified by suction filtration. The product was repeatedly subjected to the above ultrasonic treatment-suction filtration three times, and then washed with deionized water and ethanol until the filtrate was neutral. After drying in an oven at 60°C, the phthalocyanine-like polymer was obtained.

[0125] (2) Preparation of Fe / N / C oxygen reduction catalyst:

[0126] 500 mg of the phthalocyanine-like polymer obtained in step (1) was placed in a clean porcelain boat and placed in a high-temperature tube furnace. Under the protection of nitrogen, it was first programmed to 920°C at a rate of 2°C / min and held for 3 h, and then programmed to 25°C at a rate of 10°C / min. Subsequently, acid washing and drying were performed to obtain the Fe / N / C oxygen reduction catalyst, which was named Fe-N-C-6.

[0127] 2. Performance test

[0128] Step I: 4 mg of the Fe-N-C-6 oxygen reduction catalyst was added to 1000 μL of a dispersion liquid prepared from 250 μL of ethanol and 750 μL of distilled water, and ultrasonically treated for 20 min. After adding 20 μL of nafion and ultrasonically treating for another 20 min, an ink-like slurry was formed;

[0129] Step II: Another 20 μL of the ink-like slurry was taken and dropped on a foam nickel (1 cm x 1 cm), and allowed to dry completely;

[0130] Step III: The oxygen evolution reaction electrocatalytic performance of the sample was tested in 0.1 mol / L KOH aqueous solution with high-purity graphite carbon rod as the counter electrode, Ag / AgCl as the reference electrode, and the foam nickel dried completely in step II as the working electrode. The test results are shown in Figure 4 , and the overpotential was 950 mV vs. RHE.

[0131] 3. Experimental results

[0132] Figure 1 The scanning electron microscope image of the Fe-N-C oxygen reduction / oxygen evolution reaction bifunctional catalyst of the present application is shown in the figure. As can be seen from the figure, the oxygen reduction / oxygen evolution reaction bifunctional catalyst prepared in Example 1 is aggregated and presents a spherical morphology; the oxygen reduction / oxygen evolution reaction bifunctional catalyst prepared in Example 2 exhibits a loose flaky stacked morphology; and the oxygen reduction / oxygen evolution reaction bifunctional catalyst prepared in Example 3 has a layered structure stacked morphology similar to graphene.

[0133] Figure 2The image shows the powder X-ray diffraction (PXRD) spectra of the Fe-NC oxygen reduction / oxygen evolution bifunctional catalyst of this invention. As can be seen from the figure, the oxygen reduction / oxygen evolution bifunctional catalysts prepared in Examples 1, 2, and 3 have similar crystal structures. Specifically, the diffraction peak at 2θ = 25.955° can be attributed to the (100) crystal plane of C3N4 (PDF#78-1693); the diffraction peaks at 2θ = 30.083° and 35.433° can be attributed to the (220) and (311) crystal planes of Fe3O4 (PDF#89-4139); and the diffraction peak at 2θ = 42.943° can be attributed to the (220) and (311) crystal planes of Fe2N. The diffraction peaks at 2θ = 44.672°, 65.021°, and 82.333° can be attributed to the (110), (200), and (211) crystal planes of Fe (PDF#89-7194); the peak at 2θ = 40.320° can be attributed to the (104) crystal plane of rhombohedral hexagonal Fe2O3 (PDF#88-2359). This indicates the successful synthesis of the Fe-NC catalyst and that it is a Fe3O4 / Fe2N / Fe-C3N4 composite.

[0134] Figure 3 The figures show the electrochemical performance of the Fe-NC oxygen reduction / oxygen evolution reaction bifunctional catalysts prepared in Examples 1, 2, and 3, and Comparative Examples 1 and 2 of this invention. As can be seen from the figures, the half-wave potentials of the oxygen reduction / oxygen evolution reaction bifunctional catalysts prepared in Examples 1, 2, and 3, and Comparative Examples 1 and 2 are 0.841 V, 0.827 V, 0.825 V, 0.705 V, and 0.737 V, respectively. Examples 1 and 1 show that the addition of inorganic salts affects the electrochemical performance of oxygen reduction; the half-wave potential increases significantly after the addition of inorganic salts. Examples 3 and 2 show that excessive inorganic salts also have an adverse effect on the half-wave potential. This may be because an appropriate amount of inorganic salt, acting as a high-temperature solvent and structure-directing agent, imparts reversibility to the imide formation reaction, thereby promoting cyclization. The oxygen reduction electrochemical performance of Examples 1, 2 and 3 shows that the Fe-NC oxygen reduction / oxygen evolution bifunctional catalyst with a smaller benzene ring has higher oxygen reduction electrochemical performance due to its lower π conjugation effect. This may be because the catalyst with a lower π conjugation effect has a higher π delocalized electron, which is beneficial to the adsorption of O2.

[0135] Figure 4The schematic diagram of the oxygen evolution reaction (OER) electrochemical performance of the Fe-N-C oxygen reduction / oxygen evolution reaction bifunctional catalyst of the present application is shown in the figure, and it can be seen that the overpotential of the Fe-N-C catalyst prepared by Example 1, Example 2, Example 3 and Comparative Example 3 is 651.6 mV, 447.6 mV, 488.6 mV and 950 mV, respectively. The results show that the Fe-N-C oxygen reduction / oxygen evolution reaction bifunctional catalyst with high π conjugation effect has high oxygen evolution reaction electrochemical performance, and the reason may be that the catalyst with high π conjugation effect is beneficial to the desorption of O2. Compared with the overpotential (667.6 mV) of the commonly used Pt / C catalyst on the market, Example 1 has similar oxygen evolution reaction electrochemical performance to the Pt / C catalyst, while the oxygen evolution reaction electrochemical performance of Example 2 and Example 3 is higher, and the cost of Example 1, Example 2 and Example 3 is lower than that of the Pt / C catalyst. By synthesizing the covalent organic framework in the presence of anhydrous inorganic salt and then mixing with iron salt and calcining, the oxygen reduction / oxygen evolution reaction bifunctional catalyst can be obtained, and although the Fe-N-C catalyst synthesized by the strategy of one-pot reaction and then calcination in Comparative Example 3 has excellent oxygen reduction electrochemical performance, the oxygen evolution reaction electrochemical performance is not good, and it cannot be used as a Fe-N-C oxygen reduction / oxygen evolution reaction bifunctional catalyst.

[0136] Figure 5 The schematic diagram of the zinc-air battery performance of the Fe-N-C oxygen reduction / oxygen evolution reaction bifunctional catalyst of the present application is shown in the figure, and it can be seen that the maximum power density of the Fe-N-C oxygen reduction / oxygen evolution reaction bifunctional catalyst prepared by Example 2 is 122.0 mW·cm -2 The results show that the Fe-N-C oxygen reduction / oxygen evolution reaction bifunctional catalyst with enhanced π conjugation effect can be applied to zinc-air batteries and has excellent battery performance.

[0137] In summary, the Fe-N-C oxygen reduction / oxygen evolution reaction bifunctional catalyst prepared by the present application shows excellent oxygen reduction electrochemical performance, oxygen evolution reaction electrochemical performance and zinc-air battery performance. In addition, the preparation method of the present application has the advantages of easy availability of raw materials, low equipment cost, simple operation, short time consumption and suitability for industrial production and promotion.

[0138] Finally, it should be noted that the above examples are only used to illustrate the technical solutions of the present application, and not to limit them; although the present application has been described in detail with reference to the foregoing examples, those skilled in the art should understand that they can modify the technical solutions described in the foregoing examples, or make equivalent substitutions for part of the technical features. These modifications or substitutions do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for preparing a Fe-NC bifunctional catalyst with enhanced π-conjugation, characterized in that, Includes the following steps: (1) In the presence of anhydrous inorganic salt, dianhydride and diamine are subjected to solid-phase melt reaction and freeze-dried for 5-72 h. By regulating the π-conjugation effect of organic ligands with benzene rings and / or heterocycles by inorganic salt, a covalent organic framework containing π-conjugation effect is obtained. The anhydrous inorganic salt includes at least one of anhydrous zinc chloride, anhydrous sodium chloride or anhydrous calcium chloride. The molar ratio of dianhydride, diamine and anhydrous inorganic salt is 1:(1-10):(5-15). (2) The covalent organic framework is mixed with an iron compound to obtain a mixture, wherein the mixing includes at least one of hydrothermal method, impregnation method or distillation stirring reflux method; (3) The mixture is calcined at 700-1100℃ for 2-10 h to obtain a Fe-NC oxygen reduction / oxygen evolution bifunctional catalyst with enhanced π conjugation.

2. The method for preparing the Fe-NC bifunctional catalyst with enhanced π-conjugation according to claim 1, characterized in that, In step (1), the temperature of the solid-phase melting reaction is 100℃-450℃ and the time is 1-50 h.

3. The method for preparing the Fe-NC bifunctional catalyst with enhanced π-conjugation according to claim 1, characterized in that, In step (1), the dianhydride includes at least one of pyromellitic dianhydride, 1,4,5,8-naphthalenetetracarboxylic anhydride, perylene 3,4,9,10-tetracarboxylic anhydride, 3,3',4,4'-biphenyltetracarboxylic anhydride, 1,2,3,4-cyclopentanetetracarboxylic anhydride, or 1,2,3,4-cyclobutanetetracarboxylic anhydride; the diamine includes at least one of phenylenediamine, melamine, benzimidazole diamine, 2,6-diaminopyridine, 2,4,6-triaminopyrimidine, 4,4'-diaminodiphenylmethane, or 2,2-bis[4-(4-aminophenoxy)phenyl]propane.

4. The method for preparing the Fe-NC bifunctional catalyst with enhanced π-conjugation according to claim 1, characterized in that, In step (2), the iron compound includes at least one of ferric chloride, ferric nitrate, ferric sulfate, ferric oxide, or iron(II,III) oxide.

5. A Fe-NC bifunctional catalyst with enhanced π-conjugation, characterized in that, It is prepared by the preparation method described in any one of claims 1-4.

6. The application of the Fe-NC bifunctional catalyst with enhanced π-conjugation as described in claim 5 in energy conversion devices.

Citation Information

Patent Citations

  • Fe / N / C oxygen reduction catalyst derived from phthalocyanine-like polymer carbonization, preparation method of Fe / N / C oxygen reduction catalyst, air electrode and fuel cell

    CN114899436A

  • Rich-hole nitrogen-doped graphene non-platinum catalytic material and preparation method thereof

    CN117790829A

  • Fe-N-C bifunctional catalyst as well as preparation method and application thereof

    CN118925780A